Stromal characteristics are adequate prognosticators for recurrence risk in ductal carcinoma in situ of the breast. Issue 4 (April 2019) - Van Bockstal, Mieke; Lambein, Kathleen; Smeets, Ann; Slembrouck, Laurence; Neven, Patrick; Nevelsteen, Ines; Weltens, Caroline; Van Limbergen, Erik; Christiaens, Marie-Rose; Van Ongeval, Chantal; Wildiers, Hans; Libbrecht, Louis; et al.
Abstract: Background: Ductal carcinoma in situ (DCIS) of the breast constitutes a heterogeneous group of non-obligate precursors for invasive breast cancer. To date, adequate risk stratification is lacking, which is presumed to result in overtreatment. We previously identified myxoid stromal architecture as a potential prognosticator for loco-regional recurrence. In the present study, we investigated the prognostic potential of stromal characteristics. Methods: Hematoxylin and eosin stained slides from 211 DCIS patients were reviewed. The following histological features were dichotomously assessed: nuclear grade, DCIS architecture, presence of necrosis, intraductal calcifications, stromal inflammation and myxoid stromal architecture. Loco-regional recurrences constituted the primary endpoint. Results: Cox regression analysis showed that high nuclear grade, myxoid stromal architecture and moderate to extensive stromal inflammation were significantly associated with decreased recurrence-free survival, independent of radiotherapy. Based on these features, a combined risk score (CRS) was calculated, ranging from zero to three. A high CRS of three was associated with significantly shorter recurrence-free survival. Nineteen patients had a CRS of three, of which three relapsed (15.7%), whereas only one out of 113 patients with a CRS of zero relapsed (0.9%). Conclusions: We were able to validate our previously reported findings regarding the prognostic potential of myxoid periductal stroma in an independent DCIS patient cohort. A CRS based on nuclear grade, myxoid stromal architecture and stromal inflammation might facilitate discrimination of low risk from high risk patients. Consequently, the CRS may tailor adjuvant therapy. Future research should investigate whether radiotherapy can be safely omitted in patients with a low CRS.